2019
DOI: 10.1093/intimm/dxz014
|View full text |Cite
|
Sign up to set email alerts
|

BATF2 prevents T-cell-mediated intestinal inflammation through regulation of the IL-23/IL-17 pathway

Abstract: Inappropriate activation of the IL-23 signaling pathway causes chronic inflammation through the induction of immunopathological T h 17 cells in several tissues including the intestine, whereas adequate T h 17 responses are essential for host defense against harmful organisms. In the intestinal lamina propria, IL-23 is primarily produced by innate myeloid cells including dendritic cells (DCs) and macrophages (Mϕs). However, the molecular mechanisms underlying the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…h Proposed mechanism scheme of BATF2 in GC. The m 6 A modification of BATF2 mRNA by METTL3 represses its expression; BATF2 promotes the expression of p53 by suppressing its ubiquitination and degradation, which further decreased ERK signaling Accumulating evidence has shown that BATF2 plays an important role in cell cycle regulation, EMT, inflammatory responses, and resistance to therapies [7,16,17]. In accordance with previous studies, we found that BATF2 acts as a multifunctional protein that inhibits GC growth and metastasis both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…h Proposed mechanism scheme of BATF2 in GC. The m 6 A modification of BATF2 mRNA by METTL3 represses its expression; BATF2 promotes the expression of p53 by suppressing its ubiquitination and degradation, which further decreased ERK signaling Accumulating evidence has shown that BATF2 plays an important role in cell cycle regulation, EMT, inflammatory responses, and resistance to therapies [7,16,17]. In accordance with previous studies, we found that BATF2 acts as a multifunctional protein that inhibits GC growth and metastasis both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 90%
“…Accumulating evidence has shown that BATF2 plays an important role in cell cycle regulation, EMT, inflammatory responses, and resistance to therapies [ 7 , 16 , 17 ]. In accordance with previous studies, we found that BATF2 acts as a multifunctional protein that inhibits GC growth and metastasis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…During T cruzi infection, SARI functions as a negative regulator of IL‐23a in innate immune cells . We and a previous study by Kayama also demonstrated the protective role of SARI in colitis through regulating macrophage infiltration …”
Section: Introductionsupporting
confidence: 71%
“…Focusing on the gene expression data, we found that different combinations of the four TFs led to increased expression of several genes involved in the regulation of T cell homeostasis, activation, proliferation, differentiation and function (Figure 4A ), such as IRF family members ( Irf1 , Irf2 , Irf5 , Irf7 and Irf9 (Hammami et al, 2015; Hida et al, 2000; Martinet et al, 2015; Simon et al, 1997; Zhou et al, 2012)), JAK-STAT signaling pathway members ( Jak1 , Jak2 , Stat1 , Stat2 and Stat5a (Seif et al, 2017)), SOCS family members ( Socs1 , Socs2 and Socs4 (Palmer and Restifo, 2009) ), cytokine signaling ( Tgfb1 , Il2rb , Ifngr1 and Il17ra (Curtsinger et al, 2012; Oh and Li, 2013; Ross and Cantrell, 2018; Tosello Boari et al, 2018)) and other factors ( Atf3 , Batf2 , Ets2 , Gadd45a , Klf4 , etc. (Filén et al, 2010; Kayama et al, 2019; Salvador et al, 2005; Yamada et al, 2009; Zaldumbide et al, 2002)). To more systematically evaluate these transcriptional effects, we created a gene signature consisting of genes that are the most differentially expressed (up or down) between untreated fibroblasts and CD8+ T cells (using DESeq2; see Methods ).…”
Section: Resultsmentioning
confidence: 99%